A ribosome-interacting jumbophage protein associates with the phage nucleus to facilitate efficient propagation. - Wichanan Wannasrichan; Sucheewin Krobthong; Chase J Morgan; Emily G Armbruster; Milan Gerovac; Yodying Yingchutrakul; Patompon Wongtrakoongate; Jörg Vogel; Chanat Aonbangkhen; Poochit Nonejuie; Joe Pogliano; Vorrapon Chaikeeratisak (PLoS Pathogens)
Bacteriophages must hijack the gene expression machinery of their bacterial host to efficiently replicate. Recently, we have shown that the early-expressed protein gp014 of Pseudomonas nucleus-forming phage phiKZ forms a stable complex with the host ribosomes and modulates the overall protein expression profile during phage infection. Here, we discover a nucleus-forming phage, designated Churi, that is closely related to phiKZ. Churi encodes gp335, a homolog of gp014-phiKZ, which is expressed during the early stages of infection, and its overexpression in bacterial cells interferes with bacterial growth, suggesting its role in phage-host interplay. We predict experimentally that gp335 also interacts with host ribosomal proteins, similar to its homolog gp014-phiKZ, thereby strengthening its involvement in protein translation during phage infection. We further show that GFP-tagged gp335 specifically localizes by clustering around the phage nucleus and remains associated with it throughout the infection cycle. The CRISPR-Cas13-mediated deletion of gp335 reveals that the mutant phage fails to replicate efficiently, resulting in an extended latent period. Altogether, our study demonstrates that gp335 is an early-expressed protein of the Chimallivirus Churi that localizes in proximity to the phage nucleus, likely serving a role in localized translation to ensure efficient phage propagation.